Resource Utilization of Oilfield Sludge (Turning Waste into Value), A Review - Rehman Farooq; Muhammad Usman Amjad; Rizwan Akbar; Sania Riaz; Muhammad Haris Malik; Faheem Ahmad (Asian Journal of Mechanical Engineering, 2025)
The demand for energy and oil extraction is being driven by the continually rising worldwide production of petroleum. The production of oily sludge, a byproduct of the extraction, transportation, storage, and refining of crude oil, has also increased as a result of this expansion. There are serious health and environmental hazards associated with oily sludge, that consists of a complex mixture of solid particles, water, petroleum hydrocarbons, and hazardous compounds. Because oily sludge contains dangerous substances like polycyclic aromatic hydrocarbons (PAHs) and heavy metals, it is categorized as hazardous waste in many nations. Effective treatment and disposal of oily sludge is a crucial environmental concern since incorrect disposal or untreated sludge can seriously contaminate land, water, and air. Over 60 million tons of oily sludge are produced annually worldwide; in recent years, China has produced more than 6 million tons. This study looks at a variety of methods for treating oily sludge, including physical, chemical, biological, and thermal processes. The study also highlights how important it is becoming to develop cost-effective and eco-friendly methods for removing oily grime. Treatments covered include pyrolysis, solvent extraction, solidification, biodegradation, incineration, and other advanced oxidation processes (AOPs). Despite the wide variety of ways, each has its own advantages and disadvantages. The study emphasizes the need for a multi-tiered approach that integrates many technologies to recover valuable resources such as petroleum hydrocarbons and reduce the environmental impact of oily sludge. The effectiveness, scalability, and cost implications of each treatment method are critically assessed in this paper